The analysis of WIG20 stock index in R: a case study - Kotyra, B.; Krajka, A. (Математичне моделювання в економіці, 2014)
In this short note we would like to show the basic methods of analyzing time series. This methods leads us to the different models of time series (decomposition, ARIMA, Fourier techniques, exponentially smoothing and GARCH). The correctness of the models obtained may be verified by behavior of residuals (small variance, stationary, uncorrelated, normally distributes) or by verifying the predictions. This second method not will be discussed here. We omit the lot of data mining methods, which may be applied to the stock index time series, such as neural networks and genetic algorithms. У представленій роботі коротко наведені методи аналізу часових рядів. Ці методи дозволяють розробити різноманітні моделі часових рядів (розкладання, ARIMA, метод Фур’є, експонентне згладжування та GARCH). Точність отриманих моделей можна перевірити за допомогою нев’язок (невеликі відхилення, стаціонарні, корелювання та некорелювання) або шляхом верифікації прогнозів (це не представлене у даному дописі). Також не розглядаються багато методів інтелектуального аналізу даних, які можуть бути застосовані до фондового індексу часових рядів, наприклад, нейронні мережі та генетичні алгоритми. В данной работе коротко представлены методы анализа временных рядов. Эти методы позволяют разработать различные модели временных рядов (разложение, ARIMA, метод Фурье, сглаживание по экспоненте и GARCH). Точность полученных моделей можно проверить с помощью невязок (небольшие отклонения, стационарные, коррелированные и некоррелированные) или путем верификации прогнозов (что не будет здесь представлено). Мы опускаем также множество методов интеллектуального анализа данных, которые могут быть применены к фондовому индексу временных рядов, такие как нейронные сети и генетические алгоритмы.